2015
DOI: 10.1007/978-3-662-46706-0_24
|View full text |Cite
|
Sign up to set email alerts
|

Branching Heuristics in Differential Collision Search with Applications to SHA-512

Abstract: Abstract. In this work, we present practical semi-free-start collisions for SHA-512 on up to 38 (out of 80) steps with complexity 2 40.5 . The best previously published result was on 24 steps. The attack is based on extending local collisions as proposed by Mendel et al. in their Eurocrypt 2013 attack on SHA-256. However, for SHA-512, the search space is too large for direct application of these techniques. We achieve our result by improving the branching heuristic of the guess-and-determine approach to find d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…In addition, there are negligible memory requirements. Most importantly, combined with the use of automated techniques [MNS11,MNS13,EMS14] to solve the nonlinear differential characteristic for RIPEMD-160, improved SFS collision attacks for reduced RIPEMD-160 are obtained, as specified below.…”
Section: Our Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are negligible memory requirements. Most importantly, combined with the use of automated techniques [MNS11,MNS13,EMS14] to solve the nonlinear differential characteristic for RIPEMD-160, improved SFS collision attacks for reduced RIPEMD-160 are obtained, as specified below.…”
Section: Our Contributionsmentioning
confidence: 99%
“…In a word, the differential characteristic located at X i (13 ≤ i ≤ 17) and X i (36 ≤ i ≤ t) should be as sparse as possible. Then, we can solve the nonlinear differential characteristic located at X i (18 ≤ i ≤ 35) with the use of automated techniques [MNS11,MNS13,EMS14]. The desirable discovered differential characteristics are displayed in Table 12, Table 13, Table 14 and Table 15 in Appendix A respectively.…”
Section: Differential Characteristicsmentioning
confidence: 99%
“…In 2011, Mendel et al [38] extended it for SHA-256 which was further improved in their work in 2013 [39]. Eichlseder et al [19] improved upon the branching heuristics of this tool and applied it to SHA-512. Recently Stevens et al [49] presented a parallelized search implementation and found free-start collision on full SHA-1.…”
Section: Related Workmentioning
confidence: 99%
“…The best known collision attacks on SHA-256 so far are semi-free-start collisions for 38 and collisions for 31 out of 64 steps by Mendel et al in [20]. Recently, Eichlseder et al presented semi-free-start collisions for SHA-512 on up to 38 steps in [8]. Compared with the preimage attacks, all these attacks have practical complexities.…”
Section: Introductionmentioning
confidence: 99%